2015
DOI: 10.1161/circoutcomes.114.001662
|View full text |Cite
|
Sign up to set email alerts
|

What Is in a Name?

Abstract: Abstract-Despite major advances in treating hypertension, >50% of all individuals diagnosed with the condition remain in poor control. A fundamental issue may be that patients may not fully understand the meaning of the term hypertension or its cause, leading to poor adherence to medications and limiting other effective self-management behaviors. We posit that the word hypertension itself may contribute to these misunderstandings, particularly in regards to the role of stress in causing hypertension, which thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Consistent with findings that lay labels are perceived as less severe, less representative of disease, and more prevalent (Young et al, 2008), patients also felt a physician's use of lay labels indicated that the disease was less worrisome and would subside quickly (Ogden et al, 2003). Based on this growing body of work, physicians should also avoid instances where particular labels may be misinterpreted and as a result, undermine treatment (Bokhour and Kressin, 2015). The optimal terminology to be used by physicians in consultations depends on the language used by patients and the intended outcome.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Consistent with findings that lay labels are perceived as less severe, less representative of disease, and more prevalent (Young et al, 2008), patients also felt a physician's use of lay labels indicated that the disease was less worrisome and would subside quickly (Ogden et al, 2003). Based on this growing body of work, physicians should also avoid instances where particular labels may be misinterpreted and as a result, undermine treatment (Bokhour and Kressin, 2015). The optimal terminology to be used by physicians in consultations depends on the language used by patients and the intended outcome.…”
Section: Discussionmentioning
confidence: 62%
“…Ethical issues with regards to language choice arise when language is shown to readily bias perceptions and health behavior intention. Bokhour and Kressin (2015) expressed a similar concern toward potentially misinterpreted disorder labels, like hypertension, suggesting individual labels may carry their own semantic and cognitive biases. Despite being an established medical label for high blood pressure due to elevated arterial tension, hypertension is often misinterpreted as excessive general tension or stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The advice given during the hospitalization regarding aftercare and need for medication therapy seems to have been eroded by perceived side effects and information from TV commercials, as well as his own beliefs about his conditions and what might help treat them. This is not uncommon ; patients often hold different views about their conditions and effective treatments than the biomedical model 63, 64 . For example, our and others’ work has revealed that many patients view hypertension as a stress-induced condition which can be remedied by lifestyle changes to reduce stress 54, 63 .…”
Section: The Cases: Two Different Patients Illustrate the Varying Infmentioning
confidence: 99%